Nutzung der keramischen Glühkerze als Sensorelement - Demirdelen, Ismet (Forschungsberichte aus der Industriellen Informationstechnik, 2024)
This work presents methods for using the ceramic glow plug as a sensor element. This means that the ceramic glow plug will not only perform its conventional task as a heating element but will also provide information, such as motor speed, from the combustion chamber as a sensor. The main focus will be on the change in resistance, particularly under the influence of a temperature change, in the immediate vicinity of the ceramic glow plug.